Research of the corporate network information protection system based on GNS3 - Галата, Лілія Павлівна; Корнієнко, Богдан Ярославович (Science-based technologies, 2020)
A study of the information protection system of a corporate network based on GNS3 was performed. A simulation model of the corporate network protection system based on GNS3 has been built. The GNS3 program is a graphical network emulator that allows you to simulate a virtual network that consists of network equipment of more than twenty different manufacturers on a local computer, and connect a virtual network to a real network. The corporate network information protection system consists of Gateway, Firewall, Digital Signature Verifier and Logger microservices. We used elements that will allow us to test the protection system as a complete simulation model. A software package was developed using ASP.NET Core technology. The application architecture is implemented using the design pattern of "microservice architecture". Each element of the protection system, its role, functions and implementation are considered. SQL Injection and Cross-site scripting threat protection was implemented. Digital signature verification provides an additional layer of information security. The response of the corporate network information protection system to a threatened request is presented. Logging was analyzed using the Logger microservice, protection analysis will further identify weak points of protection and develop improvements. Conducted stress tests using the Vega program (to fulfill the goals of the attacker, the Kali Linux software operating system was chosen) showed that the system is very resistant to attacks such as SQL Injection and Cross-site scripting. A simulation model of the corporate network protection system based on GNS3 using a digital signature of a minimum size with a specified level of stability has been developed. Statistical data on the reaction of the information protection system are analyzed. Conclusions are drawn about the effectiveness of the developed information protection system in the corporate network.